Intimate Partner Violence in Nicaragua: The Role of Possessive Jealousy, Intrasexual Competitiveness, Life History, Mate Value, and Stress - Buunk, Abraham P. (Journal of interpersonal violence, 2021)
Using an evolutionary perspective, we examined predictors of intimate partner violence (IPV) in the Department of the Rio San Juan in Nicaragua. Specifically, we focused on possessive jealousy, intrasexual competitiveness, life history strategy, mate value, and stress. The sample consisted of 199 men and 201 women (mean age = 36.48, SD = 10.47) from the general population who were all personally interviewed. For all variables, validated measures were used. The data were analyzed for men and women separately, using regression analyses. In contrast to previous research and our expectations, possessive jealousy was not related to IPV among men or women. Rather, among men, IPV was independently predicted by (a) intrasexual competitiveness, (b) a fast life history strategy, (c) a low mate value, and (d) stress, together explaining 35% of the variance. Among women, violence against one’s partner was only predicted by intrasexual competitiveness (3% explained variance). These results suggest that perpetration of IPV in Nicaragua may have qualitative different roots among men than among women, and that for men, more “triggers” are present which may evoke aggression toward their partners. These results are discussed in light of their relevance for theory and practice.